LEGAL MECHANISMS FOR SUSTAINABLE DEVELOPMENT AND ENVIRONMENTAL CONTROL - Luminița DIACONU (Legea și Viața)
This article delves into the critical role of legal mechanisms for environmental control and assessment in fostering sustainable development. The aim of the study is to elucidate how monitoring, evaluating, and regulating environmental factors are essential for achieving long-term sustainability across various sectors. The methodology employed includes a comprehensive review of existing literature and best practices in environmental control and assessment, initiation of expertise, presentation of project documentation, environmental assessment documentation, as well as other necessary documentation. The process of examining the documentation and Issuance of the opinion Major findings/Results emphasize the role of integrating legal mechanisms in environmental considerations into decision-making processes for a more sustainable future. The paper emphasizes the significance of legal mechanisms monitoring for environmental control and in mitigating the impact of human activities on the environment and promoting sustainable practices for a harmonious coexistence between development and nature.